2011
DOI: 10.1007/s00455-011-9352-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hyoid and Laryngeal Displacement in Video Fluoroscopic Swallowing Studies: Variability, Reliability, and Measurement Error

Abstract: Video fluoroscopy is commonly used in the study of swallowing kinematics. However, various procedures used in linear measurements obtained from video fluoroscopy may contribute to increased variability or measurement error. This study evaluated the influence of calibration referent and image rotation on measurement variability for hyoid and laryngeal displacement during swallowing. Inter- and intrarater reliabilities were also estimated for hyoid and laryngeal displacement measurements across conditions. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…This size-of-the-system parameter (C2-4 length) did indeed vary significantly by participant sex, with greater size-of-the-system in men. It is important to note that previous work has suggested that a fixed 15mm reference value can be assigned to the C3 vertebrae (Kim & McCullough, 2008; Sia, Carvajal, Carnaby-Mann, & Crary, 2011). While our data revealed that the mean size of C3 in our sample was remarkably close to this suggested referent (14.98mm), these values demonstrated a SD of +/− 2.49mm.…”
Section: Discussionmentioning
confidence: 99%
“…This size-of-the-system parameter (C2-4 length) did indeed vary significantly by participant sex, with greater size-of-the-system in men. It is important to note that previous work has suggested that a fixed 15mm reference value can be assigned to the C3 vertebrae (Kim & McCullough, 2008; Sia, Carvajal, Carnaby-Mann, & Crary, 2011). While our data revealed that the mean size of C3 in our sample was remarkably close to this suggested referent (14.98mm), these values demonstrated a SD of +/− 2.49mm.…”
Section: Discussionmentioning
confidence: 99%
“…Sia, Carvajal, Carnaby-Mann, and Crary (2012) pointed out that "radial distortion causes an image to be increasingly stretched toward the periphery" (p. 192) of the field of view. Although videofluoroscopy allows visualization of articulatory gestures and swallowing function, the spatial resolution offered by the technique may not be sufficient to detect the smallest changes in articulatory positioning induced by different body positions.…”
Section: Study Limitationsmentioning
confidence: 99%
“…If a patient is not seated at precisely 90 degrees to the camera, or is tilting their head or shoulders, this can result in image distortion and shadows that make it difficult to clearly define structural boundaries (Sia et al . ). One situation that poses a clear challenge with respect to spatial resolution is the measurement of residue severity.…”
Section: Introductionmentioning
confidence: 97%